1980
DOI: 10.1038/bjc.1980.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prostaglandin analogues on epithelial cell proliferation and xenograft growth

Abstract: Summary.-The influence of two prostaglandin (PG) analogues, 16,16-dimethyl PG E2 and 16,16-dimethyl PG F2, and of the cyclo-oxygenase inhibitor, flurbiprofen, on epithelial cell proliferation was assessed using a stathmokinetic technique. The epithelia examined were those of the jejunal crypts, the colonic crypts and that of dimethylhydrazine-induced adenocarcinomas of rat colon. The influence of the two prostaglandin analogues, and of flurbiprofen, oi the growth of a human colorectal tumour propagated as xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Attempts have also been made to assess the influence of PG on colonic epithelial proliferation in vivo. It has been reported that acute parenteral administration of the PG analogs 16,16-dimethyl PGE2 or 16,16-dimethyl-PGF2a failed to alter the proliferative activity of colonic crypt epithelium in normal rats when assessed 4 h after injection of these agents (7). Similarly, the cyclooxygenase inhibitor flubiprofen was without apparent effect on the proliferative activity of colonic crypts, when assessed 4 h after injection of this drug (7).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Attempts have also been made to assess the influence of PG on colonic epithelial proliferation in vivo. It has been reported that acute parenteral administration of the PG analogs 16,16-dimethyl PGE2 or 16,16-dimethyl-PGF2a failed to alter the proliferative activity of colonic crypt epithelium in normal rats when assessed 4 h after injection of these agents (7). Similarly, the cyclooxygenase inhibitor flubiprofen was without apparent effect on the proliferative activity of colonic crypts, when assessed 4 h after injection of this drug (7).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that acute parenteral administration of the PG analogs 16,16-dimethyl PGE2 or 16,16-dimethyl-PGF2a failed to alter the proliferative activity of colonic crypt epithelium in normal rats when assessed 4 h after injection of these agents (7). Similarly, the cyclooxygenase inhibitor flubiprofen was without apparent effect on the proliferative activity of colonic crypts, when assessed 4 h after injection of this drug (7). These negative results are difficult to interpret, since (a) no evidence was provided that the systemic administration of either of the PG analogs or the cyclooxygenase inhibitor altered local colonic PG levels; and (b) proliferative activity was examined only after a brief period of in vivo exposure to the test agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these properties plausibly make h-escin a prime candidate for a potential cancer chemopreventive agent. For instance, prostaglandin-F 2 a strongly inhibited cell proliferation in dimethylhydrazineinduced rat colon adenocarcinoma (17), and compounds with anti-hyaluronidase activity are associated with an increased resistance to tumors (18). Matsuda et al (19) reported the inhibitory effect of escins isolated from horse chestnut on carrageenan-induced hind paw edema in an animal model for acute inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A similar tendency to inhibit proliferation has been observed in a rat colon tumour model after treatment with 16,16-dimethyl-PGE 2 . Both in the normal colonic mucosa and in the tumour, a reduction of mitotic index was observed in the highest PG-dose group mediated by an increase of cAMP (Tutton and Barkla, 1980). Prostaglandin E 2 effects in min-mice are mediated by the PG receptors EP2 and 4, which signal via cAMP.…”
Section: Discussionmentioning
confidence: 93%